Control of a Wind Generation System Based on a Brushless Doubly-Fed Induction Generator Fed by a Matrix Converter - Muñoz-Lagos, A (ELSEVIER SCIENCE SA, 2013)
The Doubly-Fed Induction Generator (DFIG) is one of the most widely used generators for wind energy applications with more than 50% of installed Wind Energy Conversion Systems (WECS) using this variable speed technology. However, the conventional DFIG requires brushes and copper slip-rings to connect a power converter to the rotor windings. The use of brushes decreases the WECS robustness and extra maintenance is required to periodically inspect/replace these elements. In this work a new topology for a Brushless Doubly-Fed Induction Generator (BDFIG) is presented. As an alternative to conventional Voltage Source Inverters (VSI) a matrix converter is used to regulate the current supplied to the stator of the doubly-fed machine, supplying the excitation energy to the WECS. The proposed generation system is mathematically analysed in this paper and the design of the control loops is discussed. Because the power spectrum density of the wind speed is dominated by low frequency components, in this work some simplifications of the transfer functions of the system are proposed. Experimental results obtained from a 3 kW prototype of a cascaded DFIG, are presented and fully discussed. © 2013 Elsevier B.V. All rights reserved.